2009
DOI: 10.1080/01421590802216241
|View full text |Cite
|
Sign up to set email alerts
|

Educational effectiveness of a personal digital assistant-based geriatric assessment tool

Abstract: Residents who used a personal digital assistant-based geriatric assessment tool demonstrated greater improvement in geriatric knowledge than peers who did not use this resource. Curricula adapted to this technology may prove useful in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In terms of secondary outcomes, for medical education interventions, one trial reported two outcomes regarding documentation of health care problems [19] and four trials reported nine knowledge outcomes [16],[18],[19],[21]. For clinical diagnosis and management interventions, seven trials [28],[30],[33]–[37] reported 25 outcomes relating to appropriate management (3 outcomes), testing (3) [28], referrals (1) [28], screening (4) [33], diagnosis (2) [34],[35], treatment (2) [35],[36], and triage (10) [37].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of secondary outcomes, for medical education interventions, one trial reported two outcomes regarding documentation of health care problems [19] and four trials reported nine knowledge outcomes [16],[18],[19],[21]. For clinical diagnosis and management interventions, seven trials [28],[30],[33]–[37] reported 25 outcomes relating to appropriate management (3 outcomes), testing (3) [28], referrals (1) [28], screening (4) [33], diagnosis (2) [34],[35], treatment (2) [35],[36], and triage (10) [37].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies randomized participants into 2 groups [28-39,41-45,47-55]. Furthermore, 1 study randomized participants into 3 groups [46] and 2 studies randomized participants into 4 groups [27,40]. Participants included preregistration and postregistration health professionals.…”
Section: Resultsmentioning
confidence: 99%
“…The interventions are described in Multimedia Appendix 10. All interventions used PDAs in developed countries (Austria [270], Canada [271], and US [272-274]). In these interventions the technology was used to enhance students' pharmacological and clinical contextual knowledge in both clinical practice and nursing education [270], and to determine a patient’s stage of change, providing scripted motivational interviews targeted to their stage, and making relevant health behavior and stage-based interventions immediately accessible [273].…”
Section: Resultsmentioning
confidence: 99%